PENGARUH PROMOSI JABATAN TERHADAP KINERJA KARYAWAN PADA PT. RIAU MEDIA GRAFIKA/ TRIBUN PEKANBARU - Simanjuntak, Winda Yulyarta; ", Kasmiruddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research is to know the effect of Job Promotion towards Employees Performance in the PT. Riau Media Grafika/ Tribun Pekanbaru.This research used questionnaire with measurement scale that is Likert scale which analyzed by validity test, reliability test, simple regression analysis, t test, and correlation analysis and determination with the help of using SPSS software ver. 22 for windows. The number of population from this research 137 persons with 58 employees which consists of employees of business units and employees editorial unit on PT. Riau Media Grafika/ Tribun Pekanbaru as the sample, which calculated by Slovin formula.From the results of tests performed indicate that the Job Promotion has positive and significant impact on Employees Performance of Tribun Pekanbaru. Which is the determination coefficient values shown that the variable of Job Promotion constribute to variable of Employees Performance by 83,2% while the remaining 16,8% is influenced by other variables outside the model.Keywords : Human Resource Management, Job Promotion, Employees Performance